GOVERNMENT DOCUMENT STORAGE INFORMATION SYSTEM FOR THE OFFICIAL INFORMATION CENTER, KHONKAEN GOVERNOR’S OFFICE - Butkhot, Teerapat; Preecha, Nakarin (SciTech Research Journal, 2019)
The purpose of this research is to: 1. To reduce the duplication of work 2. to keep the information neat and easy to be used for use 3. to facilitate the fast recording of government documents Government document storage system. 5. To create a government document storage program. The researcher created a questionnaire to evaluate the satisfaction with the system of collecting official documents by using a questionnaire that Can be obtained from a group of system users who have helped to develop in the organization Is the Chief Correspondent of the City Hall and employees within the organization By showing the mean and standard deviation Assessment of user satisfaction in all aspects of the system The results of the evaluation showed that the satisfaction of the system users in all aspects of the managers and individuals in the organization were satisfied at the highest level With an average value of 4.66, with a standard deviation of 0.12 Found that all aspects were satisfied at the highest level